(untitled) (Research, Society and Development, 2026)
Thrombotic Microangiopathy (TMA) is an uncommon and life-threatening condition characterized by microangiopathic hemolytic anemia, thrombocytopenia, and endothelial injury, frequently associated with acute kidney injury (AKI). Early recognition remains clinically challenging due to overlapping manifestations with other nephrological and hematological disorders, as well as limited access to confirmatory diagnostic tests. This study aimed to critically analyze the available evidence regarding the main diagnostic and therapeutic challenges of TMA associated with AKI. This is a narrative literature review with a descriptive and qualitative approach. The literature search was conducted in November 2025 in the PubMed and LILACS databases using MeSH terms related to thrombotic microangiopathy, acute kidney injury, diagnosis, and treatment, combined with Boolean operators. Studies published between 2015 and 2025 in Portuguese, English, and Spanish were included, encompassing clinical guidelines, clinical trials, meta-analyses, reviews, and observational studies. The analyzed studies demonstrate relevant advances in the understanding of TMA pathophysiology, particularly regarding the role of the complement system and the use of biomarkers and genetic testing to refine diagnostic accuracy. Clinical benefits were observed with the early initiation of targeted therapies, such as plasma exchange and complement inhibitors, with favorable impact on morbidity, mortality, and preservation of renal function. In conclusion, timely identification and a multidisciplinary approach are essential to optimize clinical management and improve patient outcomes.